THE EFFECT OF E-GOVERNMENT AND TRANSPARENCY OF REGIONAL BUDGET MANAGEMENT ON THE LEVEL OF CORRUPTION IN PROVINCIAL GOVERNMENT IN INDONESIA - Anindiyadewi, Nabila Carissa; Susilowati, Endah (Yayasan Education and Social Center, 2023)
This research aims to examine the influence of e-government and transparency of regional budget management on the level of corruption in provincial governments in Indonesia. The type of research used in this research is a quantitative approach. The population in this research is all 38 local governments in Indonesia. The research sample was selected using a purposive sampling method with several criteria, such as having an official website, the website being accessed, and having SPI data. The number of samples in this research was 34 provinces. This research uses secondary data obtained through the official website of the provincial government in Indonesia and the Integrity Assessment Survey results report. The analysis technique used in this research is SmartPLS 3.0. The research results show that e-government affects corruption in provincial governments in Indonesia. In contrast, transparency of regional budget management does not affect the level of corruption in local governments in Indonesia. This research implies that each local government in Indonesia can improve the quality of e-government implementation so that it can reduce corruption cases that occur in each province